Kedudukan Gratifikasi Seksual dalam KUHP Nasional: Studi Komparatif Hukum Pidana Indonesia dan Singapura - Sabrina Gita Salsabella; Nadea Lathifah Nugraheni; Praditya Arcy Pratama (Jurnal Hukum Lex Generalis, 2026)
Sexual gratification enforcement in Indonesia faces legal ambiguity. This study examines its position in Indonesian criminal law through a comparative study with Singapore. Using normative methods and a socio-legal approach, findings show that Indonesia's "other facilities" phrase in Article 12B of the AntiCorruption Law causes legal uncertainty and evidentiary difficulties. Conversely, Singapore’s Prevention of Corruption Act (PCA) applies a broad interpretation of "undue advantage," covering all subjective benefits, including sexual services, supported by established jurisprudence. This research recommends a transformation toward substantial justice in Indonesia.